2016
DOI: 10.31018/jans.v8i2.927
|View full text |Cite
|
Sign up to set email alerts
|

Advent of Trichoderma as a bio-control agent- A review

Abstract: Trichoderma spp are free living filamentous fungi. They are cosmopolitan and versatile in nature. They have the potential to produce several enzymes that can degrade the cell wall materials. Also, they release a number of fungi toxic substances that can inhibit the growth of the fungal pathogens. Many mechanisms have been described on how Trichoderma exert beneficial effects on plants as a bio-control agent. But due to its versatile nature, its potential cannot be explored to its full extent. And it is a devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…The mechanism of attack of Fusarium oxysporum is to penetrate, colonize, and multiply in the root area, then parasitize and inhibit the process of carrying water to all parts of the plant, this is confirmed by [4], that the mechanism of inhibition carried out by Trichoderma harzianum against Fusarium oxysporum is a mechanism of parasitism.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…The mechanism of attack of Fusarium oxysporum is to penetrate, colonize, and multiply in the root area, then parasitize and inhibit the process of carrying water to all parts of the plant, this is confirmed by [4], that the mechanism of inhibition carried out by Trichoderma harzianum against Fusarium oxysporum is a mechanism of parasitism.…”
Section: Introductionmentioning
confidence: 81%
“…Trichoderma harzianum is a fungus that can inhibit the growth of other fungal pathogens by releasing a number of toxic fungal substances and producing several enzymes that can degrade cell walls [4]. Tricoderma harzianum has been widely used as a biocontrol agent to suppress soil-borne pathogens, according to [5], the Trichoderma harzianum F116 strain has the most effective antagonistic activity against Fusarium oxysporum and has the potential for biological control.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, previous studies have determined that Trichoderma species (e.g., T. akoningii , T. asperlloides , T. atroviride , T. harzianum, T. lentiforme, T . longibrachiatum , and T. virens ) successfully controlled various fungal plant pathogens including the fungal genera Alternaria , Cladosporium , Fusarium , Phytophthora , and Stagonosporopsis ( Puyam, 2016 ; Ghazanfar et al, 2018 ; Sood et al, 2020 ; Thapa et al, 2020 ). Furthermore, Utkhede and Koch (2004) and Patel et al (2017) found that T. harzanum could significantly reduce the effects of gummy stem blight disease caused by S. cucurbitacearum in cucurbit plants under both greenhouse and field conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of Trichoderma spp. in inhibition of plant pathogenic could be attributed to different mechanisms such as mycoparasitism and competition with the pathogens for space and nutrients as well as due to the production of antibiotics such as Gliotoxin and Viriden and lysis enzymes such as B-1,3-gluconase, Chitinase and Protease (Harman et al, 2004;Gajera et al, 2012;Vinale et al, 2012;Puyam, 2016). Activity of some Trichoderma spp.…”
Section: Discussionmentioning
confidence: 99%